PROFILING STUDENTS’ EXPERIENCES AND PERSPECTIVES ON USING VIDEO-TELECONFERENCING APPLICATIONS AS A LEARNING PLATFORM DURING PANDEMIC - Maulana, Endrian; Daud, Afrianto; Masyhur (International Journal of Educational Best Practices, 2022)
This study aims to capture students’ profiles in terms of using video-teleconferencing (VTC) applications  and to identify students’ perspectives on using the video-teleconference applications as a platform for English teaching and learning during pandemic in the English department in Universitas Riau. This mixed method study collected data from semi-structured interviews and an online questionnaire. The entire sophomores of English Study Program of Riau University (n=39 students) were taken as the samples of the research. An analysis model from Miles & Huberman (2007) was used as the method to analyze the collected data. The results show that majority (56.4 %) of the students used mobile phone for  learning device and 59% of them relied on their own internet data for learning. The students had both positive and negative perspectives on the VTC applications. Most students thought the VTC based learning was efficient for them. However, they  reported some problems such as, unsupportive learning environment, lack of equipment, and unreliable internet connections. These problems imply that the universities should provide more learning facilities for students to make the online learning more effective.